Artificial intelligence design research on the cyber security penetration testing of power grid enterprises. (October 2019) - Sun, X D; Ren, Z; Yang, P W; Li, J; Chen, H Y; Liu, T Q
Abstract: This paper introduces the key components of Artificial Intelligence (AI) expert system. It studies the main application of AI technology in network security. It deeply analyzes the network security situation of power grid enterprises, as well as the main problems in the troubleshooting and verification of vulnerability. The AI penetration test expert system is designed, and the implementation of the system is elaborated.